Designing a Coaching Model for Managers of Iranian Governmental Organizations with Emphasis on Sustainable Human Resources - Zare Zeidi, Alireza; Jafari Kalarijani, Seyyed Ahmad; Mehrara, Asadollah; Bagherzadeh, Mohammadreza (Digital Transformation and Administration Innovation, 2025)
Supportive coaching promotes individual development and organizational effectiveness, emphasizing nurturing and learning. Leading organizations utilize skilled managers not only as successful leaders but also as proactive coaches to enhance productivity and reduce costs. The aim of this study was to design a coaching model for managers of Iranian governmental organizations with a focus on sustainable human resources. This research employed a qualitative methodology, and the participants included faculty members specializing in organizational behavior management and human resource management in higher education institutions, senior managers and experts in human resource management in governmental organizations, and specialists with awareness of the research topic. Using the snowball sampling method, 15 experts were selected. Data collection was conducted through semi-structured interviews. For data analysis, thematic analysis based on the six-phase approach of Clarke and Braun (2006) was used through three stages: initial coding, theme development, and theme refinement, utilizing Atlas.ti software. To ensure validity and reliability, necessary assessments were conducted using Holsti’s coefficient, Scott’s Pi coefficient, Cohen’s Kappa index, and Krippendorff’s Alpha. The level of agreement among experts, calculated via Holsti’s coefficient (observed agreement percentage), was estimated at 0.887; Scott’s Pi index at 0.755; Cohen’s Kappa at 0.725; and Krippendorff’s Alpha at 0.817. Based on the findings, the final model consists of seven main themes: 1) personal and professional characteristics of the coach, 2) coaching process, 3) knowledge-orientation, 4) organizational transformation, 5) technology and equipment, 6) interactivity, and 7) support and resources—comprising 22 sub-themes and 135 indicators.